Effect of a gene for high dough strength on whole wheat baking parameters of hard white spring wheat. Issue 3 (13th March 2018) - Sherman, Jamie D.; Varella, Andrea C.; Lanning, Susan P.; Martin, John M.; Heo, Hwa‐Young; Nash, Deanna; Blake, Nancy K.; Cook, Jason P.; Talbert, Luther E.
Abstract : Background and objectives: Whole wheat flour has weaker mixing properties and produces bread with smaller loaf volume than bread made from white flour. The objective of this research was to test the effect of an allele for increased dough strength on the quality of bread made from whole wheat flour. Findings: An allele for increased strength at the Gli‐B1 locus was introduced by backcrossing into four hard white spring wheat backgrounds. Whole wheat flour was used for a mill and bake analysis with near‐isogenic lines containing alternative alleles at Gli‐B1 grown in dryland and irrigated environments. The allele for strong gluten did not impact flour protein. However, the strong gluten allele resulted in increased dough strength and greater loaf volume in near‐isogenic lines from different genetic backgrounds and under multiple environments. Conclusions: The allele for strong gluten at Gli‐B1 may be useful to improve the end‐use quality of hard white wheat for the purpose of making whole wheat leavened bread. Significance and Novelty: Introgression of specific genes for gluten proteins may positively impact baking quality of whole wheat.